Club foot treatment in Malawi - a public health approach. - Lavy, C; Mannion, S; Mkandawire, N; Tindall, A; Steinlechner, C; Chimangeni, S; Chipofya, E (2007)
PURPOSE. Malawi is a very poor country with a current population of 12 million people and very few orthopaedic surgeons or physiotherapists. An estimated 1125 babies are born per year with club foot. If these feet are not corrected early, then severe deformity can develop, requiring complex surgery. A task force was established to address this problem using locally available resources. METHODS: A nationwide early manipulation programme was set up using the Ponseti technique, and a club foot clinic established in each of Malawi's 25 health districts. One year later the clinics were reviewed. RESULTS: Twenty out of the 25 clinics originally established were still active, and over one year had seen a total of 342 patients. Adequate records existed for 307 patients, of whom 193 were male and 114 female (ratio 1.7:1). A total of 175 patients had bilateral club foot and 132 were unilateral (ratio 1.3:1) giving a total of 482 club feet; 327 of the 482 feet were corrected to a plantigrade position. Most clinics had problems with supply of materials. Many patients failed to attend the full course of treatment. CONCLUSIONS: Overall the establishment of a nationwide club foot treatment programme was of benefit to a large number of children with club feet and their families. In a poor country with many demands on health funding many challenges remain. The supply of plaster of Paris and splints was inadequate, clinic staff felt isolated, and patient compliance was limited by many factors which need further research.